Pesky home networks trouble cable behemoths. - Cherry, S.M.
Are wireless router users stealing broadband Internet access? The author discusses the application of the NAT (network address translation ) protocol into wireless routers which allows several computers to share a single Internet address. Wireless networks using NAT connect with a cable or DSL modem and then the whole wireless network has Internet access
Keywords: DSL; Internet address; NAT; Broadband Internet access; Cable modem; Digital subscriber line; Network address translation protocol; Wireless networks; Wireless router